Data associated with 'Oral tribology, adsorption and rheology of alternative food proteins' - Kew, Ben; Holmes, Mel; Stieger, Markus; Sarkar, Anwesha (University of Leeds, 2021)
Raw data for all figures in the associated paper 'Oral tribology, adsorption and rheology of alternative food proteins'
Keywords: FOS: Health sciences; FOS: Biological sciences